To speak, or not to speak – do clinicians speak about dying and death with geriatric patients at the end of life? (Swiss Medical Weekly, 2012)
QUESTIONS UNDER STUDY: Research describing healthcare professionals' conversations about issues of dying and death with chronically ill geriatric patients is rare, especially in Europe. The study reviews the willingness and difficulties of physicians and nurses to speak about dying and death with geriatric patients. METHOD: Interview study with 14 physicians and 17 nurses. RESULTS: The majority (21/31) of the interviewed physicians and nurses reported a considerable willingness to speak about dying and death with patients approaching the end of life. Obstacles to addressing this topic included external circumstances such as lack of time and/or privacy (14/31); personal reasons, such as feeling confronted with one's own mortality (12/31); resistance or denial in their patients (12/31); and the cognitive state of the patients (7/31). CONCLUSIONS: Discussing and preparing (the patient) for an end-of-life decision early enough is a prerequisite of good palliative care. It is an ethical obligation on the side of the healthcare professionals to support openness, respect for autonomy, and dignity by addressing issues of dying and death with the patient in order to help facilitate advance care planning.